The Neodymium Stable Isotope Composition of the Oceanic Crust: Reconciling the Mismatch Between Erupted Mid-Ocean Ridge Basalts and Lower Crustal Gabbros - McCoy-West, Alex J.; Millet, Marc-Alban; Burton, Kevin W. (Frontiers in Earth Science, 2020)
The trace element and isotopic compositions of mid-ocean ridge basalts (MORB) provide an important cornerstone for all studies seeking to understand mantle evolution. Globally there is a significant over-enrichment in the incompatible trace element concentrations of MORB relative to levels which should be generated by fractional crystallization. Thermal and geochemical constraints suggest that MORB require generation in open system magma chambers. However, the petrology of lower oceanic crustal rocks suggests instead that these enrichments maybe formed through reactive porous flow (RPF). Stable isotope compositions are process dependent and therefore provide an excellent mechanism to compare these contrasting models. This study presents the first neodymium (Nd) stable isotope compositions of Indian MORB and well characterized gabbroic rocks from the lower oceanic crust sampled at the Southwest Indian Ridge (Hole 735B). Indian MORB is extremely homogenous with a mean δ146Nd of −0.025 ±0.005‰ which is identical to the composition of Pacific MORB. Despite significant variability in the source composition of MORB globally (i.e. 143Nd/144Nd) their indistinguishable δ146Nd compositions suggests they were homogenized through the same process along the global ridge network. In stark contrast, oceanic gabbros have δ146Nd ranging from −0.026‰ to −0.127‰, doubling the natural variability in Nd stable isotopes observed in terrestrial rocks. Clinopyroxene separates possess variable δ146Nd but are isotopically heavier than the gabbroic whole rocks at the same major element compositions. These large variations in δ146Nd cannot be generated solely by the fractionation or accumulation of clinopyroxene and/or plagioclase. Hole 735B preserves widespread evidence of RPF which could induce kinetic isotopes fractionation during crystal growth. In clinopyroxene kinetic isotope fractionations will only induce ca. 0.02‰ variations therefore several cycles of dissolution and reprecipitation of isotopic signatures at grain boundaries are required to explain the range of δ146Nd observed in the gabbros. Given the large disconnect between the average composition of the lower crust (δ146Nd = −0.076‰) and MORB globally and the evidence of limited melt extraction into the upper crust at Hole 735B it is highly unlikely that the melts involved in RPF contributed in a substantial way to the Nd isotope composition of erupted MORB.